(untitled) (LACCEI, 2024)
Abstract– Pineapple (Ananas comosus) is one of the most consumed fruits worldwide. Its industrial processing generates a large amount of agri-food waste, and among these, the peel represents a high percentage. Pineapple peel is a rich source of phenolic compounds with widely demonstrated antioxidant and anti-inflammatory properties. In this study, the technical feasibility of developing hydrogels with potential cosmetic applications through the incorporation of bioactive compounds extracted from pineapple peel was evaluated. Taking the above into account, different formulation tests were carried out until a product with the expected physical characteristics for a potential cosmetic topical application was found. The obtained hydrogel was synthesized using agarose as a matrix, hyaluronic acid as a crosslinker, and PEG 200-pineapple peel extract as a source of phenolic compounds. Using the FTIR spectroscopic technique, the correct cross-linking and addition of the bioactive compounds to the polymer matrix was demonstrated through significant signals at wave numbers 805, 1670, and 3500 cm-1. Finally, the release profile of the hydrogel was evaluated by HPLC-DAD, observing that the compound that exhibited a higher release rate was syringic acid. The results obtained demonstrated that the synthesis of the hydrogel added with phenolic compounds obtained from the pineapple peel was successful. This work will contribute to reducing the wastage of pineapple peel, transforming it into valuable cosmetic products.